Стиловите на лидерство во различни културни услови - Биновска Кочева, Ана (Економски факултет, УКИМ, Скопје, 2014)
Beauty is in the eye of the beholder, and each eye sees a different beauty. In this sense, leadership is like beauty – relative. Whether an individual will be perceived as a leader depends on the degree to which his characteristics and behaviors fit the inner set of values of the observer, i.e. the follower. The values are shared among the members of different groups – teams, organizations, communities, societies, and they affect their attitudes towards leadership. The leadership style that is considered to be highly effective in one culture can prove to be highly ineffective in other cultures. The findings from the international research GLOBE, based on the attributes that contribute for a leader to be outstanding, show that the same characteristics and behaviors that in some societies can be viewed as promoting good leadership, in other societies are impeding good leadership. Their research shows that the charismatic/value based leadership is universally endorsed as leadership style that greatly contributes to outstanding leadership while the other styles are culturally contingent. The research conducted for this paper, shows that in Macedonia, the charismatic leadership style stands out as the most desirable style of leadership. This style is also desirable by the Macedonian managers as well as from the managers in other countries included within the international research. Team oriented leadership, according to Macedonian managers contribute to outstanding leadership, but in Macedonia this leadership is considered to be less effective than in other countries from the world. The self-protective leadership is the least desirable leadership style by our managers, but in comparison with other countries, it is rated as more positive. The autonomous style of leadership doesn’t inhibit the outstanding leadership but in a certain sense, it slightly encourages the outstanding leadership in the Macedonian companies. The participative leadership in Macedonia slightly contributes toward outstanding leadership, while the humane oriented leadership is more desirable than this style.
The Leadership Styles in Diverse Cultural Context
Докторска дисертација одбранета во 2014 година на Економскиот факултет во Скопје, под менторство на проф. д–р Љубомир Дракулевски.
Keywords: leadership, global leaders, leader attributes, implicit leadership theory, culture, cultural dimensions, international management, international business